Promoting Islamic Values Related to Social Etiquette through Islamic Creed – An Analytical Study – - Ahmed, Prof. Dr. Awad Jadoua Ahmed; Yahya, Prof. Dr. Salman Aboud Yahya (Sulaimani Journal for Humanities, 2026)
This research, entitled “Promoting Islamic Values Related to Social Etiquette through Islamic Creed – An Analytical Study”, aims to shed light on the strong relationship between Islamic creed (‘aqeedah’) and social etiquette, and how the creed contributes to reinforcing and rooting these values in individuals. The significance of this study lies in its contribution to a deeper understanding of Islamic values and their role in shaping both individuals and society, while also offering solutions to strengthen these values in contemporary communities. Ultimately, it aspires to help build more cohesive and harmonious Islamic societies. The research addresses a key problem: the noticeable decline in Islamic values related to social etiquette. To investigate this issue, the study adopts a descriptive and analytical methodology. The study arrives at several key findings. It confirms that a sound Islamic creed serves as a compass that guides human behavior and defines individual values. It acts as a fortified shield protecting social and moral values and preserving the cultural identity of the Muslim Ummah. Furthermore, Islamic values represent a unifying identity for Muslims and serve to strengthen social bonds. The creed is not only a source of these values but also complements and integrates with them. Additionally, the creed forms the spiritual foundation of social development. It motivates individuals toward effort and creativity, unites them, and reinforces societal cohesion. Finally, the study emphasizes that Islamic values—such as modesty (ḥayā’), compassion, knowledge, and love—are essential pillars for social development, contributing to the construction of a balanced civilization based on justice and equality.
Keywords: Islamic Values; Social Etiquette; Islamic Creed; Social Development; Identity; Morality